Two-Sector Aggregative Models and the Investment Demand Function - Woglom, Geoffrey (American Economic Review, 1977)
Dale Henderson and Thomas Sargent (hereafter H-S) and Y. C. Park have analyzed the effectiveness of monetary and fiscal policy in the two-sector analogue of James Tobin's dynamic aggregative model. Contrary to the assumptions of Tobin's model, fiscal policy can affect real income in the H-S model. However, the sign of the effect of fiscal policy on real income depends on a number of conditions relating to the parameters of the money demand function and the capital intensities in the two sectors. A somewhat more disturbing result is that the sign of the effect of fiscal policy changes as one changes, ceteris paribus, the assumption of which sector is the more capital intensive. The H-S results seem to imply that the analysis of the effectiveness of fiscal policy in the traditional ISLM analysis is very sensitive to the assumption of a one-sector production technology. It is important to realize, however, that the H-S model differs from IS-LM analysis in two ways. Besides assuming a two-sector production technology, the H-S model also assumes a perfect capital market, where the asset value of capital is always equal to reproduction cost. Sargent and Neil Wallace have analyzed a one-sector model with and without the perfect capital market assumption (without and with a disequilibrium investment demand function). They find that many of the strange results of Tobin's model are eliminated if there are costs of adjusting the capital stock. For example, if the costs of adjustment are large enough, expansionary monetary policy lowers the interest rate as in IS-LM analysis, contrary to Tobin's results. Also, the stability conditions of the model imply that with costs of adjusting the capital stock, fiscal policy affects income and interest rates in much the same way as in IS-LM analysis. This paper alters the H-S model to allow for an investment demand function based on costs of adjustment.' In analyzing the comparative static results of this model one can determine whether the strange results of the H-S model are due to the assumption of a two-sector production technology or the assumption of a perfect market in existing capital goods. The profit-maximizing subsystem in the H-S model can be solved to yield the price level and the marginal product of capital as functions of the relative price of investment (see the Appendix). A general equilibrium occurs when the consumption good, money,2 and investment good markets are in equilibrium.